Difficulties in the Use of Arabic Vocabulary (Mufradāt) in Conversation among Eighth-Grade Students at MTs Mu’allimin UNIVA Medan - Rizka Adillah Lesmana; Ihsan Satrya Azhar (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This study aims to examine the difficulties in the use of Arabic vocabulary (mufradāt) in conversation among eighth-grade students at MTs Mu’allimin UNIVA Medan. The study employed a descriptive qualitative approach, with the Arabic language teacher and several eighth-grade students serving as key informants. Data were collected through observation, interviews, documentation, and triangulation. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through credibility testing, triangulation, reliability, and confirmability.The findings reveal that students’ difficulties in Arabic conversation are systemic in nature, involving less communicative teaching methods, psychological factors such as low self-confidence, and the limited availability of a language practice environment. Unlike previous studies that discussed Arabic learning difficulties in general, this study specifically focuses on the use of mufradāt in conversational contexts at the Islamic junior high school (MTs) level. This study contributes theoretically to the field of Arabic language learning difficulties and practically by providing recommendations for the implementation of communicative teaching strategies. Mastery of mufradāt has proven to be a crucial component in improving speaking skills (mahārah al-kalām). Therefore, teachers need to design interactive learning activities through dialogues, discussions, and conversation practice, while also creating a supportive learning environment to help students become more active and confident in using Arabic.